Essential clinical guide to understanding and treating autism - Volkmar, Fred R.; Wiesner, Lisa A. (Hoboken, New Jersey : Wiley, 2017)
Coauthored by the premier expert on autism in the United States and an experienced academic and practicing pediatrician, this volume provides concise and practical information based on the most up-to-date research and clinical experience for primary care givers around the world. Showing clinicians how to most effectively use evidence-based techniques, this invaluable guide offers primary-care providers access to expert, current research and practice guidelines allowing them to confidently support children who present with symptoms of autism.
What is autism : history, causes, and current research -- Screening and diagnostic assessment -- Approaches to providing medical care -- Frequent medical conditions and problems -- Working with attorneys and other referral sources -- Securing services -- Infants and preschool children -- School-aged children -- Adolescents and adults -- Behavioral and psychiatric problems : issues and interventions -- Considering medications for behavioral and mental health problems -- Considering complementary and alternative treatments -- Supporting families.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Autism -- Treatment; Autism spectrum disorders -- Treatment; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Autism spectrum disorders -- Treatment; Autism -- Treatment; Autistic Disorder -- therapy; Autism Spectrum Disorder -- therapy; Autism Spectrum Disorder -- psychology; Autistic disorder -- Psychology; Adolescent; Adult; Child; Humans; Infant; Electronic books